TRAINING OF THE CONTENT OF GEOMETRIC CONSTRUCTION CALCULATIONS IN SCHOOL AND UNIVERSITY IN THE PROCESS OF TRAINING FUTURE MATHEMATICS TEACHERS - Мадияров, Нурлыбай; Турсынкулова, Элмира; Көкеш, Ажар (Pedagogy and Psychology, 2023)
At the present stage, the organization of the educational process in secondary school on the updated content of education in accordance with modern requirements also sets new tasks for the methodological system of school education, giving each student the necessary geometric knowledge. This should be focused on the content of school geometric education, the implementation of the principle of continuity and continuity of teaching the geometry course. The comprehensive mastery of the geometry course by students depends on the degree of geometric and methodological training of the school mathematics teacher. Therefore, the University monitors the continuity of the proposed educational programs and curricula in the training of future specialists and provides an opportunity for professional training of future specialists. The article discusses the problem of continuity of teaching geometric construction problems in pedagogical universities and schools. The topics of geometric construction problems studied at schools and pedagogical universities were studied and the features were identified. The role and importance of geometric construction problems in high school, the ways of substantive and procedural development of continuity in teaching "geometric construction problems" in pedagogical universities and schools, the functions of their implementation are shown. When conducting research work, methods of pedagogical analysis, Control, Survey, pedagogical experiment were used in the content of geometric construction problems. As a result of the research, a corrective experiment was carried out to implement mutual continuity in the content of geometric construction problems in schools and universities.